EFEKTIVITAS PENGGUNAAN TEKNIK CLUSTERING TERHADAP PENINGKATAN KETERAMPILAN SISWA DALAM MENULIS KARANGAN DESKRIPSI (INSYA) - Supriadi, Rinaldi (Departemen Pendidikan Bahasa Arab, 2018)
This research is motivated by the ability of students who are still relatively weak in terms of writing using Arabic. Though their intensity to learn Arabic is more than that of students in public high schools that have Arabic learning in it. One technique that can be used in learning to write descriptive essays or in Arabic is in clustering techniques. In this technique there are several stages for writing a description or in writing, wherein with this technique students get inspiration in their minds to pour into their wills. In this study, researchers used a Quasi-experimental method, with Non-Equivalent Control Group Design. In this study, researchers selected experimental group members and control group members each of 30 people. Furthermore, the experimental group was treated as a clustering technique, while the control group did not receive the same treatment using the lecture method. Thus there is a positive and significant relationship and influence on the ability of God willing to use clustering techniques